A perfect day - Smith, Lane (Two Hoots, 2017)
A warm, funny picture book about the perfect summer's day, from beloved author and illustrator Lane Smith. It's a perfect day for everyone. Cat is lounging among the daffodils. Dog is sitting in the wading pool, deep in the cool water. Chickadee is eating fresh seed from the birdfeeder. Squirrel is munching on his very own corncob.
Keywords: eläimet